Analisis Kinerja Sprinkler Otomatis Berbasis Sensor Kelembapan dengan Optimalisasi Sudut Panel Surya - Maulidiyah, Nurul; Maulana, Yusuf (Jurusan Teknik Elektro Politeknik Negeri Pontianak, 2025)
The development of technology in the field of electrical engineering and renewable energy provides great opportunities for the application of automation systems in agriculture. One of the common problems faced by farmers is the irrigation process, which is often carried out manually, requiring significant time, labor, and electrical energy consumption. This study aims to design and evaluate an automatic sprinkler system based on soil moisture sensors powered primarily by solar panels. The system employs an Arduino Uno as the main controller, a soil moisture sensor to detect soil conditions, and a water pump as the actuator for irrigation. Energy is supplied by a solar cell connected to a charging module and a battery as the power storage unit. The research method includes hardware design, software programming, and performance testing of the system under various solar panel tilt angles (30°, 37°, 45°, 53°, and 60°). The evaluation focuses on measuring the water discharge rate, irrigation time, and the efficiency of energy harvested from the solar panel. The results demonstrate that the tilt angle of the solar panel significantly influences irrigation performance. The optimal tilt angle was found at 45°, achieving a maximum discharge rate of 24.1 ml/s, which provides the most efficient irrigation compared to other angles. Although the discharge rate varies across different tilt angles, the total water volume delivered remains relatively constant, indicating that the difference is mainly reflected in the irrigation duration. In conclusion, the proposed automatic sprinkler system based on soil moisture sensors and solar energy offers an effective, efficient, and environmentally friendly solution to support sustainable agriculture. This study also contributes to the achievement of SDGs Goal 15 (Life on Land) by promoting renewable energy utilization and automation in agricultural land management.